A simple biological imaging system for detecting viable human circulating tumor cells - Kojima, Toru (American Society for Clinical Investigation, 2009)
The presence of circulating tumor cells (CTCs) in the peripheral blood is associated with short survival, making the detection of CTCs clinically useful as a prognostic factor of disease outcome and/or a surrogate marker of treatment response. Recent technical advances in immunocytometric analysis and quantitative real-time PCR have made it possible to detect a few CTCs in the blood; however, there is no sensitive assay to specifically detect viable CTCs. Here, we report what we believe to be a new approach to visually detect live human CTCs among millions of peripheral blood leukocytes, using a telomerase-specific replication-selective adenovirus expressing GFP. First, we constructed a GFP-expressing attenuated adenovirus, in which the telomerase promoter regulates viral replication (OBP-401; TelomeScan). We then used OBP-401 to establish a simple ex vivo method that was able to detect viable human CTCs in the peripheral blood. The detection method involved a 3-step procedure, including the lysis of rbc, the subsequent addition of OBP-401 to the cell pellets, and an automated scan using fluorescence microscopy. OBP-401 infection increased the signal-to-background ratio as a tumor-specific probe, because the fluorescent signal was amplified only in viable, infected human tumor cells, by viral replication. This GFP-expressing virus-based method is remarkably simple and allows precise enumeration of CTCs.